Slavery and the Dutch economy, 1750–1800. (2nd January 2021) - Brandon, Pepijn; Bosma, Ulbe
ABSTRACT: This article presents the first methodologically grounded calculation of the weight of Atlantic slave-based activities in the Dutch economy of the second half of the eighteenth century. In this period, the Dutch Republic was one of the most developed commercial societies in Europe. The import, processing and export of slave-produced goods such as sugar, coffee and tobacco played an important role in this economy. In 1770, 5.2% of the GDP of the Dutch Republic and 10.36% of the GDP of its richest province Holland was based on Atlantic slavery. In this year, 19% of Dutch imports and (re-) exports consisted of goods produced by the enslaved in the Atlantic. These high percentages were dependent on the prominent role that the Dutch Republic and the province of Holland in particular played in Atlantic slavery-based commodity chains. These chains ran from the provisioning of slave ships in the Dutch Republic, through the slave trade, to the plantations, the transport of tropical products to Europe, their processing in the Dutch Republic, to their final export to the European hinterland. As much as 40% of all the growth of the economy of Holland in the decades around 1770 can be traced back to slavery.